METODE MODELLING THE WAY UNTUK MENINGKATKAN HASIL BELAJAR SAINS SISWA KELAS III SD - Bayu Aditama, Wiranda; Mukarromah, Aenullael (Institut Agama Islam Sahid (INAIS) Bogor, 2024)
This research aims to improve the science learning outcomes of third grade elementary school students through the application of the modeling the way method.The subjects of this research were 26 grade III elementary school students consisting of 16 male students and 10 female students. The method in this research is classroom action research which is carried out in two cycles where each cycle consists of several stages, including planning, implementation, observation and reflection. Data on student learning outcomes is obtained from written tests at the end of each cycle, while teacher and student activities are obtained from observation instruments. Indicators of success in learning outcomes are said to have increased if ≥ 85% of students get a score of ≥ 65, while indicators of success in teacher activities are at least in the good category and indicators of student activity are at least in the